RESPON PERTUMBUHAN SELEDERI PADA BUDIDAYA ORGANIK TERHADAP PENGGUNAAN JENIS NAUNGAN DAN MEDIA TANAM YANG BERBEDA - Nurlianti Nurlianti; Prihanani Prihanani (University of Prof. Dr. Hazairin, SH, 2016)
The study aims to find the planting medium and the type of shade is best for the growth of celery grown organically. Research has been conducted between May and August 2015 held at the Village Panorama City Subdistrict Singaran Pati Bengkulu. The research method using a split plot design with the main plot and subplot type of shade is kind of growing media. Conclusion The study shows the plant celery cultivated organically showed the best response to the media's treatment bokhasi with a composition of 100% bokhasi without soil mix both material waste oil mapun waste chaff (A and D), while a given soil mixture (B and C) the results are not better because of growing media becomes denser. The combination of media with bokhasi 100% (A and D) without soil can be maintained under the auspices of the Annual plants (N2) and under the auspices of zinc or terrace house (N3). Keywords: naungan, media tanam, bokhasi